A comprehensive tool for discovering and analyzing business strategies (2015)
The paper discusses strategic planning as a critical process for organizations to align long-term goals with actionable strategies while navigating competitive and uncertain environments. It highlights the theoretical importance of strategies in aligning vision with goals and practical applications in adapting to real-world challenges, particularly in high-uncertainty industries. However, existing tools for strategy formulation face issues such as excessive complexity, lack of adaptability to emerging trends, and vague definitions. To address these limitations, the paper proposes a structured, adaptable catalogue of business strategies integrated into a practical tool. This tool aims to simplify decision-making, ensure relevance to evolving contexts, and enhance strategic planning. The paper also outlines its methodology, literature review, structural principles, and practical applications, concluding with insights and future research directions.